ON THE ISSUE OF SPLITTING MULTIPLE FREQUENCIES OF FREE OSCILLATIONS OF THE ROTOR ON THE ELASTIC SHAFT - Мейш, Юлія; Бєлова, Марина (SWorldJournal, 2024)
Thin-walled rotors have a complex geometric shape caused by the branching of their meridional cross-section and the combination of shells of negative Gaussian curvature, cylindrical and conical shells, as well as disks, blades and rings into one system. T